COMPARATIVE ANALYSIS OF THE “PERFECT HUMAN” FIGURE IN THE WORKS OF NIZAMI AND NAVOIY FROM THE PERSPECTIVE OF ECOLOGICAL AWARENESS AND HARMONY WITH NATURE - Mamadaliyev , Ulug‘bek; Turg‘unboyeva , Nuriza (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article presents a comparative study of the figure of the “perfect human” (insan‑i kamil) as depicted in Nizami Ganjavi’s and Alisher Navoiy’s Khamsa within the framework of ecological awareness and harmony with nature. In traditional interpretations, the ecological dimension of this figure has often been overlooked; however, its significance is increasing in light of contemporary climate change, the loss of biodiversity, and the scarcity of natural resources. The study employs comparative literary analysis, philosophical interpretation, and contemporary ecological theoretical approaches. The findings indicate that Nizami portrays the perfect human through mystical unity with nature, while Navoiy emphasizes balance achieved through labor and ethical conduct. The scientific contribution of this research lies in being the first to examine this theme comparatively in an ecological context and to connect it with modern theoretical perspectives.